The Contributory Pension Scheme (Cps) and Sufficiency of Retirement Benefit of the Low Income Retirees of the Federal Public Service in Nigeria - Abere Omotayo Johncally; Banjo Kudirat Adeola; Saka Toyin Shafau (MultiTech Publisher, 2023)
This study examined the level of sufficient retirement benefits under the contributory pension scheme emanating from the pool of savings contributed that can suffice to provide the minimum needed livelihood at retirement. The theories adopted for the study are the Pension Funding Policy and the Life Cycle Hypothesis. The secondary data of all pension contributions and retirement benefits were retrieved from series of publications of PenCom from the years 2004 to 2022. The primary data population consists of 1316 retirees. EasyFit 5.6 Professional Software together with the Least Square Model, accumulation and annuity formulae was employed to analyse the secondary data and the responses from the respondents during survey. EasyFit Software generated statistics using the Kolmogorov Smirnov, Anderson Darling and Chi-Square Models and ranked each model statistics generated to determine the best fit for both the data and the probability distribution used. Arising from the data collected and the analysis carried out using the Consolidated Public Service Salary Structure, the level of comfort of low income retirees who spent 20 to 35 years in active service is nothing to write home about due to insufficient pension benefits as a result of the challenges (such as investment and management of pension fund restrictions, political will and bureaucratic corruption) investigated. The study recommends the implementation of minimum pension derived with requisite modalities of 20 years as the minimum qualifying length of service and only 10-year post retirement subsidy